Embodied aesthetics : proceedings of the 1st International Conference on Aesthetics and the Embodied Mind, 26th-28th August 2013 - Scarinzi, Alfonsina. (Philosophy of History and Culture, 2014)
This volume discusses the role of embodiment in the reevaluation of aesthetics as a process of bodily mediated meaning-making. It focuses on the bodily basis of aesthetic appreciation from an evolutionary point of view, on the bodily physical structures such as the brain involved in perception, on aesthetic experience and appreciation, on the role of physiological responses in experiencing the objects of the environment aesthetically, on the role of one's own body in motion in the engagement with the environment, on somatic responses and the experience of meaning, on the pre-reflective experience of the body, on the role of the interplay of different types of physical and sensory activities in the process of education to art appreciation.